2018
DOI: 10.1177/0149206318816162
|View full text |Cite
|
Sign up to set email alerts
|

It’s Not Personal: A Review and Theoretical Integration of Research on Vicarious Workplace Mistreatment

Abstract: Recent advancements in the area of workplace mistreatment have begun to challenge our view of who is affected by this phenomenon. Whereas it was initially assumed that mistreatment affected a small subset of employees who were directly targeted by negative treatment, empirical work has documented that employees who observe or become aware of others being mistreated are also adversely affected. However, the extant literature examining vicarious mistreatment has developed in silos centered around individual mist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
144
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(148 citation statements)
references
References 104 publications
(162 reference statements)
4
144
0
Order By: Relevance
“…Third, Dhanani and LaPalme pointed out in the review literature that, although some empirical studies have examined the negative impact of peer abusive supervision on the attitude and behavior of third parties, few studies focus on the mediating mechanism of third parties' emotions in the above process [15]. Hence, the current study is a timely response to the call of Dhanani and LaPalme.…”
Section: Theoretical Implicationsmentioning
confidence: 93%
See 2 more Smart Citations
“…Third, Dhanani and LaPalme pointed out in the review literature that, although some empirical studies have examined the negative impact of peer abusive supervision on the attitude and behavior of third parties, few studies focus on the mediating mechanism of third parties' emotions in the above process [15]. Hence, the current study is a timely response to the call of Dhanani and LaPalme.…”
Section: Theoretical Implicationsmentioning
confidence: 93%
“…It lays a cognitive foundation for the choice of the implicit behavior of silence of the subsequent third parties. Furthermore, this paper responds to the call for paying attention to the mediating role of the emotional reactions of third parties, between peer abusive supervision and their behavioral choice [15]. Drawing affective events theory, we construct a model of emotional mechanism between peer abusive supervision and third parties' silence, and suggest that peer abusive supervision affects silent behavior indirectly by triggering workplace anxiety.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…More broadly, our research contributes to the literature on observed aggression and uncivil behavior at work (e.g., Porath & Erez, 2007;Rafaeli et al, 2012). Existing studies in this area have focused on witnessing a perpetrator engaging in negative behavior towards a victim (Dhanani & LaPalme, 2019) such as sexual harassment, discrimination, rudeness, aggression, and bullying, and have examined its emotional and cognitive consequences (e.g., Einarsen, Skogstad, Rørvik, Lande, & Nielsen, 2018;Rafaeli et al, 2012;Reich & Hershcovis, 2015). Our work contributes to this line of research by focusing on observing an overt disagreement between two team members in one's work team, without clearly distinguishing a perpetrator and a victim, and by investigating the motivational and behavioral mechanisms explaining the relationship between observing relationship conflict and observers' work engagement.…”
Section: Theoretical Implicationsmentioning
confidence: 71%
“…As per Kahn's (1990) theory of engagement, the threat to safety and meaningfulness and the depletion of their resources will undermine their work engagement. Indeed recent research found that employees' involvement at work was adversely affected by seeing fellow workers being mistreated (Dhanani & LaPalme, 2019).…”
Section: Introductionmentioning
confidence: 99%